El olvido por lo infantil en la ficción jurídica del niño (2011)
ABSTRACT: This article accounts for the research’s results developed at the frame of the Master in Psycho-analytic Research called The oblivion for the child-ish in the legal fiction of the child: Legislation readings of childhood protection. The motivation for this subject obeys a suspicion: the existence of a conflict between the child ideas divulged for the legal discourse and denounces made by the reality about the childhood through various social phenomenon emerging more and more powerfully in our contemporary societies. Said suspicion is shaping clearer when the legal discourse is questioned by child notion involved in the legislation of protection to the childhood more representatives of our time. Taking into account various forms where the social Other has been incorporated with the child at different cultural moments, but much more, when the psychoanalytical theory’s notions and concepts take place, it allows us to think similarly to the imaginary infantile as it is justly denied in legal discourse environment as well as in the social discourse of our time.